The radicalism of the American Revolution - Wood, Gordon S. (New York : Vintage Books, 1993)
Examines colonial society and the transformations in colonial life that resulted from the republican tendencies brought to the surface by the Revolution.
pt. I. Monarchy. Hierarchy ; Patricians and plebeians ; Patriarchal dependence ; Patronage ; Political authority -- pt. II. Republicanism. Republicanization of monarchy ; Truncated society ; Enlightened paternalism ; Revolution ; Enlightenment ; Benevolence -- pt. III. Democracy. Equality ; Interests ; Assault on aristocracy ; Democratic officeholding ; World within themselves.
Originally published: New York : A.A. Knopf, 1992.
Includes bibliographical references (pages 371-430) and index.
Keywords: United States -- History -- Revolution, 1775-1783 -- Social aspects; United States -- Politics and government -- 1775-1783.; Radicalism -- United States -- History -- 18th century; Political culture -- United States -- History -- 18th century; Political culture -- History -- 18th century -- United States; Radicalism -- History -- 18th century -- United States; United States -- History -- Social aspects -- Revolution, 1775-1783; United States -- Politics and government -- 1775-1783